Exploring the potential of cuttlebone waste to produce building lime - Ferraz, E. (2020)
The goal of this study is to find a practicable way to recycle cuttlebone waste in the production of lime. It was studied the behavior of calcium oxide obtained from the calcination of this waste at 900, 1000 and 1100 ºC and, after wet slaking, the produced lime was characterized. All the results were compared to calcium oxide or to hydrated lime obtained from commercial limestone. According to the slaking results, the waste and the limestone calcined at 1000 ºC achieved the R4 (around 13 min to reach 60 ºC) and R5 (60 ºC in 25 s) reactiv-ity class, respectively. Changing the calcination temperature to 900 or 1100 ºC did not promote an increase in the reactivity of the calcined waste. Although less reactive than the calcined limestone, the calcined cuttlebone can be transformed without significant constraint into building lime, since this construction material fulfills the relevant physic-chemical standard specifications.